The 1st Virtual Conference on Social Science in Law, Political Issue and Economic Development - Yusro, Andista Candra; Multazam, Mochammad Tanzil; Rahim, Robbi (De Gruyter, 2020)
We are delighted to introduce the Virtual Conference on Social Science In Law, Political Issue And Economic Development 2020 with theme "Realizing Society 5.0 for a Better Life". The technical program has brought researchers and practitioners around the world to a good forum for discussing, leveraging and developing all scientific and technological aspects that are relevant to economic business, education and humanities.